Adapting the CROPGRO Model to Simulate Growth and Yield of Spring Safflower in Semiarid Conditions. (1st January 2016) - Singh, Sukhbir; Boote, Kenneth J.; Angadi, Sangamesh V.; Grover, Kulbhushan; Begna, Sultan; Auld, Dick
Abstract : The importance of safflower ( Carthamus tinctorius L.) is increasing as a low input, stress‐tolerant oilseed crop around the world. Adapting a crop growth model for safflower will help to assess the feasibility of this crop under diverse environmental conditions with relatively limited field experimentation. The objective of the project was to adapt the Decision Support System for Agrotechnology Transfer (DSSAT) Cropping System Model (CSM‐CROPGRO) to simulate growth and seed yield of spring safflower. The CROPGRO template approach was used, and parameters in species and cultivar files were developed based on safflower literature and calibration to field data. The entered base temperatures for photosynthetic, vegetative, and reproductive processes of safflower ranged from 0 to 5°C while corresponding optimum temperatures varied from 19 to 40°C. Simulated results were compared with observed data collected from field experiments conducted at Clovis, NM, during 2013 and 2014. The model predicted the crop life cycle (anthesis and harvest maturity date) with relative root mean square error (RRMSE) of 0.07. Average plant biomass, head mass, head number and seed number were satisfactorily simulated when compared to observed values. Seed yield, averaged over irrigation treatments and years, was predicted as 1963 kg ha −1 compared to measured value of 1902 kg ha −1 with RRMSE of 0.12. Reasonable prediction of phenology, growth, and yield by the model adapted for safflower suggested that the CROPGRO‐safflower model is promising to simulate safflower production in semiarid climates. However, further testing of the CROPGRO‐safflower model under different environments is needed.